Menguak Esensi: Negara Hukum dalam Konstitusi: Sebuah Analisis Mendalam terhadap Perlindungan Hak-hak Warga Negara - Haromain, Rozy; Ohoiwutun, Y A Triana; Harianto, Aries (LPPM Universitas Ekasakti Padang, 2024)
Regulation of sanctions for criminal acts of human trafficking in Indonesia is specifically regulated based on Article 1 number 1 of the Law on the Eradication of Criminal Acts of Trafficking in Persons which defines human trafficking as various acts of surveillance, transportation, harboring, sending, transmitting or receiving a person in various ways for the purpose of exploitation, including sexual exploitation, with laws that cause dilemmas, especially regarding prospective Indonesian workers who are vulnerable to becoming victims of human trafficking. The research method used in this research is normative juridical using a statutory regulation approach and a context approach in answering problems. The results of the research show that the application of sanctions for criminal acts of trafficking in persons as regulated in Article 2 paragraph (1) of the Law on the Eradication of Criminal Acts of Trafficking in Persons against perpetrators who exploit victims, fraud in aggravation, sanctions are also applied to state administrators, corporations and their administrators, groups organized criminal acts of human trafficking. Legal uncertainty in the application of sanctions for criminal acts of human trafficking is a serious problem that can disrupt eradication and law enforcement. This primarily relates to legal provisions governing the crime of trafficking in persons, which is very important for effective law enforcement. This uncertainty is found in two main regulations: the Law on the Eradication of the Crime of Human Trafficking and the Law on the Protection of Indonesian Migrant Workers.